Zinc(II) and nickel(II) complexes of 3, 5‐dimethyl‐1‐(pyridin‐2‐yl)‐1H‐pyrazole: relationship between fluorescence and crystal packing. Issue 7 (7th June 2021) - Małecka, Magdalena; Kusz, Joachim; Mayer, Peter; Sobiesiak, Marta; Budzisz, Elzbieta
Abstract : The single‐crystal structures of Zn II and Ni II complexes of 3, 5‐dimethyl‐1‐(pyridin‐2‐yl)‐1 H ‐pyrazole are reported and their fluorescence properties are described. Abstract : Two novel coordination complexes, namely, dichlorido[3, 5‐dimethyl‐1‐(pyridin‐2‐yl‐κ N )‐1 H ‐pyrazole‐κ N 2 ]zinc(II), [ZnCl2 (C10 H11 N3 )], 1, and aquachloridobis[3, 5‐dimethyl‐1‐(pyridin‐2‐yl‐κ N )‐1 H ‐pyrazole‐κ N 2 ]nickel(II) chloride monohydrate, [NiCl(C10 H11 N3 )(H2 O)]Cl·H2 O, 2, have been synthesized. The crystal structure analyses revealed that complexes 1 and 2 are mononuclear and have ZnN2 Cl2 distorted tetrahedral and NiN4 OCl distorted octahedral structures, respectively. Complex 1 displays a dimer in the crystal structure, while complex 2 forms a chain along the [010] direction. The fluorescence properties of both complexes were also investigated. A search of the Cambridge Structural Database for other complexes of the ligand 3, 5‐dimethyl‐1‐(pyridin‐2‐yl)‐1 H ‐pyrazole (L ) shows that there exist different coordination polyhedra with different arrangements as monomers, dimers and polycyclic structures. Here it has also been demonstrated that there is a relationship between the crystal packing and the fluorescence properties of Zn II and Cd II complexes of L .